No evidence of disease activity in patients receiving fingolimod at private or academic centers in clinical practice: a retrospective analysis of the multiple sclerosis, clinical, and magnetic resonance imaging outcomes in the USA (MS-MRIUS) study. (3rd August 2018) - Zivadinov, Robert; Khan, Nasreen; Korn, Jonathan R.; Lathi, Ellen; Silversteen, Jason; Calkwood, Jonathan; Kolodny, Scott; Silva, Diego; Medin, Jennie; Weinstock-Guttman, Bianca
Abstract: Objective: The impact of multiple sclerosis (MS) center type on outcomes has not been investigated. This study aimed to evaluate baseline characteristics and clinical and magnetic resonance imaging (MRI) outcomes in patients with MS receiving fingolimod over 16 months' follow-up at private or academic centers in the USA. Methods: Clinical and MRI data collected in clinical practice from patients initiating fingolimod were stratified by center type and retrospectively analyzed. No evidence of disease activity (NEDA-3) was defined as patients with no new/enlarged T2/gadolinium-enhancing lesions, no relapses, and no disability progression (Expanded Disability Status Scale scores). Results: Data were collected for 398 patients from 25 private centers and 192 patients from eight academic centers. Patients were older (median age = 43 vs 41 years; p = .0047) and had a numerically shorter median disease duration (7.0 vs 8.5 years; p = .0985) at private vs academic centers. Annualized relapse rate (ARR) was higher in patients at private than academic centers in the pre-index (0.40 vs 0.29; p = .0127) and post-index (0.16 vs 0.08; p = .0334) periods. The opposite was true for T2 lesion volume in the pre-index (2.86 vs 5.23 mL; p = .0002) and post-index (2.86 vs 5.11 mL; p = .0016) periods; other MRI outcomes were similar between center types. After initiating fingolimod, ARRs were reduced, disability and most MRI outcomes remained stable, and a similar proportion of patients achieved NEDA-3 at private and academic centers (64.1% vs 56.1%; p = .0659). Conclusion: Patient characteristics differ between private and academic centers. Over 55% of patients achieved NEDA-3 during fingolimod treatment at both center types.